Standar Garis Kemiskinan Dalam Perspektif Syariah - Amin Nur Kholid (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study aims to examine the concept of the poverty line from a sharia perspective. This study uses a qualitative-descriptive approach. The primary data source is literature such as books, journals, and articles related to Islamic economics that discuss the Islamic poverty line. Meanwhile, secondary data sources come from various literature that explain the primary data sources, including books, books, journals, and articles. The results of the study indicate three things: first, determining the standard poverty line from a sharia perspective can use two approaches: the had al-kifayah approach, and the nishab approach for gold zakat and agricultural zakat. Second, calculations using the nishab standard for the zakat poverty line are much easier and more rational than conventional approaches. Third, the poverty line based on the nishab gold is higher than the poverty line according to the World Bank.